Bursal body Weight ratio and Histopathological changes in commercial chicks Vaccinated with a live and two killed Infectious bursal disease vaccines - L. Sa’idu3, M.T. Angani1, P.A Abdu2, (Journal of Medical Biomedical and Applied Sciences, 2014)
This study was conducted to compare the bursal body weight ratio and histopathological changes in commercial chicks vaccinated with a live and two killed infectious bursal disease (IBD) vaccines. Two hundred and eighty, day old chicks were divided into four groups of seventy chicks each. Group 1, 2 and 3 were vaccinated with live vaccine, killed vaccine (A) and killed vaccine (B) respectively while group 4 was not vaccinated. Vaccination was conducted at 9 and 16 days of age. Five chicks from each group were sacrificed weekly and the bursa to body weight ratio (BBWR) were determined. Twenty chicks from each group were challenged with a very virulent infectious bursal disease virus (vvIBDV) at 30 days of age. There was no significant difference in body weight in chicks vaccinated with both live and killed IBD vaccines but there was a significant decrease in the bursal body weight ratio of chicks in group 1 after vaccination at p value of 0.0001 and after challenge at p value of 0.0002. Histopathologic lesions which include; thickened epithelium, interfollicular oedema, small sized follicles, poorly demarcated cortex and medulla and follicles sparsely populated by lymphocytes were observed in the chicks in group 1. No histopathologic lesions were observed in chicks in group 2 and 3 after vaccination but lesions were observed in group 3 after challenge. No lesions were observed inÂ group 4 prior to challenge but after challenge, lesions observed include; sloughed off epithelium, interfollicular oedema, interfollicular haemorrhages, interplica debris, follicles devoid of lymphocytes. In conclusion, the live vaccine caused bursal atrophy. Killed vaccine A and B did not have any adverse effect on the BF. Killed vaccine A is recommended for the control of IBD in Nigeria and the potential of the live vaccine to cause bursal atrophy and immunosuppression should be investigated.